Mobility for learners and staff - higher education students and staff mobility inter-institutional agreement 2014-21 between programme countries Università degli Studi di Torino and Universidade Lusíada de Lisboa - Universidade Lusíada de Lisboa (2017)
- Cooperate for exchange of students and/or staff in the context of the Erasmus + programme. - Subject area: Political science